2021
DOI: 10.1371/journal.pone.0253482
|View full text |Cite
|
Sign up to set email alerts
|

Production and сharacterization of the exopolysaccharide from strain Paenibacillus polymyxa 2020

Abstract: Paenibacillus spp. exopolysaccharides (EPSs) have become a growing interest recently as a source of biomaterials. In this study, we characterized Paenibacillus polymyxa 2020 strain, which produces a large quantity of EPS (up to 68 g/L),and was isolated from wasp honeycombs. Here we report its complete genome sequence and full methylome analysis detected by Pacific Biosciences SMRT sequencing. Moreover, bioinformatic analysis identified a putative levan synthetic operon. SacC and sacB genes have been cloned and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 75 publications
(156 reference statements)
0
10
0
Order By: Relevance
“…Common to all polysaccharides, two bands are observed around the 3280–2930 cm −1 region ( Figure 4 , green): the strong broadband appearing at 3282 cm −1 represents the O-H stretching of hydroxyls’ vibrations, and the weak signal at 2923 cm −1 is due to the C-H stretching peak of CH 2 groups [ 13 , 41 ]. In addition, the IR absorption bands around 970-1145cm −1 ( Figure 4 , blue) are mainly due to C-C and C-O stretching in the pyranoid ring and C-O-C stretching of glycosidic bonds [ 42 , 43 , 44 ]. The bands observed at 1725 cm −1 ( Figure 4 , yellow) and at 1248 cm −1 may be attributed to the acyl substituents present in FucoPol’s structure, namely, the C=O stretching vibrations of carbonyls and the C-O-C vibrations, respectively [ 23 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common to all polysaccharides, two bands are observed around the 3280–2930 cm −1 region ( Figure 4 , green): the strong broadband appearing at 3282 cm −1 represents the O-H stretching of hydroxyls’ vibrations, and the weak signal at 2923 cm −1 is due to the C-H stretching peak of CH 2 groups [ 13 , 41 ]. In addition, the IR absorption bands around 970-1145cm −1 ( Figure 4 , blue) are mainly due to C-C and C-O stretching in the pyranoid ring and C-O-C stretching of glycosidic bonds [ 42 , 43 , 44 ]. The bands observed at 1725 cm −1 ( Figure 4 , yellow) and at 1248 cm −1 may be attributed to the acyl substituents present in FucoPol’s structure, namely, the C=O stretching vibrations of carbonyls and the C-O-C vibrations, respectively [ 23 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peak around 1603 cm −1 and the peaks in the region between 1400 and 1370 cm −1 ( Figure 4 , yellow and orange) may be assigned to the asymmetric and symmetric stretching of carboxylates from glucuronic acid [ 13 , 23 , 29 ]. The presence of bound water might be indicated by the bending vibration of O-H associated with a peak around 1603 cm −1 ( Figure 4 , yellow) [ 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Paenibacillus polymyxa isolated from wasp honeycombs was able to produce 2.4% (w/v) EPS with 5.0% (w/v) sucrose after 48 h (Liyaskina et al, 2021). The source and concentration of sugar in the medium affect EPS production.…”
Section: Eps Productionmentioning
confidence: 99%
“…Mamphogoro et al (2022) reported the whole-genome sequence of P. polymyxa SRT9.1, a plant growth-promoting bacterium consisting of 6,754,470 bp and 7878 coding sequences, with an average G + C content of 45% [250]. Revin and Liyaskina et al obtained a highly productive strain Paenibacillus polymyxa 2020, first isolated from wasp honeycombs capable of producing a greater amount of levan compared to the known P. polymyxa strains (Figure 3) [66]. The complete genome sequencing and methylome analysis of P. polymyxa 2020 were performed.…”
Section: Levan-producing Bacteriamentioning
confidence: 99%
“…The GC content of Paenibacillus DNA ranges from 39 to 59% [255]. Complete genome sequencing and assembly has been done for strains such as P. polymyxa E681 [257], P. polymyxa SC2 [258], P. polymyxa ATCC 842T [259], P. polymyxa 2020 (isolated from wasp honeycombs) [66], P. polymyxa KF-1, soil isolated producer of antibiotics [260], and Paenibacillus sp. Y412MC10 [247], isolated from Obsidian Hot Spring in Yellowstone National Park, Montana, USA.…”
Section: Levan-producing Bacteriamentioning
confidence: 99%